Scalable Subband Coding Of Images - Ng, Mow Song (2006)
Scalable coding of images provides an efficient solution for dissemination of visual information in heterogeneous networking and computing environments. In this coding framework, an image can be reconstructed at various resolutions and bit rates from a single bitstream, with minimal loss in rate-distortion performance. In this work, three subband image codecs, Set Partitioning in Hierarchical Trees (SPIHT), Embedded Zero Block Coding (EZBC) and Pixel Classification and Sorting (PCAS), are fully implemented for rate scalable coding initially.